2019
DOI: 10.3390/genes10010030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Grain Nutritional Traits and Leaf Blight Resistance in Rice

Abstract: Colored rice is rich in nutrition and also a good source of valuable genes/quantitative trait loci (QTL) for nutrition, grain quality, and pest and disease resistance traits for use in rice breeding. Genome-wide association analysis using high-density single nucleotide polymorphism (SNP) is useful in precisely detecting QTLs and genes. We carried out genome-wide association analysis in 152 colored rice accessions, using 22,112 SNPs to map QTLs for nutritional, agronomic, and bacterial leaf blight (BLB) resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 143 publications
1
12
0
Order By: Relevance
“…Consequently, these QTLs were detected in different environments and genetic backgrounds. The above results clearly showed the complexity of agronomic traits and grain Zn concentration 14,15,42 . Since the present study used BLUE values which excluded environmental effects and magnify genetic effects, the QTLs identified in this study may well prove more useful in rice biofortification breeding programs than the QTLs identified using single environment phenotypic values.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consequently, these QTLs were detected in different environments and genetic backgrounds. The above results clearly showed the complexity of agronomic traits and grain Zn concentration 14,15,42 . Since the present study used BLUE values which excluded environmental effects and magnify genetic effects, the QTLs identified in this study may well prove more useful in rice biofortification breeding programs than the QTLs identified using single environment phenotypic values.…”
Section: Discussionmentioning
confidence: 68%
“…However, the huge genetic variability in grain mineral nutrients available in the rice germplasm can be exploited to develop biofortified high yielding rice varieties 12 . Even though genetic complexity and G x E were reported to be a hindrance for improving mineral content with high yield, much progress has been achieved in elucidating the genetic basis and G x E effect on grain micronutrient accumulation, yield and yield related traits in rice 13,14 .…”
mentioning
confidence: 99%
“…The relation between TPC, flavonoids and AOA was studied with grain color in 481 accessions of rice with white, red and black colored genotypes and correlation studies indicated a negative correlation between a * and antioxidant capacity (33). The grain color was also found to be associated with anthocyanin and Zn content when 156 rice accessions varying in grain color were screened and analyzed through genome-wide association studies (34). Similar findings were revealed from transcriptomics and proteomics studies in colored rice (22).…”
Section: Introductionmentioning
confidence: 63%
“…The association of skin color with various nutritional parameters is well established in various vegetables and fruits (30). In food crops, the relationship between flavonoids and antioxidant activity was studied with grain color in colored rice (33,34). However, in peanut the studies are limited to studying the relation between PKS with nutraceuticals like total polyphenol content and antioxidant capacity (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…They also consistently observed qZn1.1, a QTL for zinc content, across seasons and locations. In another study involving 152 coloured rice accessions, Descalsota‐Empleo, Noraziyah, et al () identified qZn1.1. The consistent location of QTL for grain iron and zinc contents on chromosomes 1, 2, 4, 7, 10, 11 and 12 across various genetic backgrounds and environments indicates that these QTL are useful for breeding biofortified crops.…”
Section: Discussionmentioning
confidence: 98%